Avaliação termo-oxidativa de óleos vegetais submetidos a temperatura de fritura: uma abordagem por ressonância magnética nuclear de hidrogênio - Nobre, Túlio Silvestre (2021)
Soybean, palm, sunflower, canola, olive and corn oils thermal behavior were evaluated at frying temperature (180 ºC) for 24 hours by nuclear magnetic resonance of hydrogen (1H NMR). Mathematical equations were applied to integrals of fingerprint signals at the 1H NMR spectrum of oils to determine fatty acid profile, iodine value, saponification value and average molecular weight. The behavior of these parameters was evaluated during heating throughout 0,12 and 24 hours, as well as the formation of primary and secondary oxidation products. The fatty acid composition results indicated high concentration of saturated fatty acids in palm oil (44.0 mol%) and a significant amount of the same fatty acid in soybean oil (20.5% mol). The oils with the highest amounts of monounsaturated oleic fatty acid were olive oil (75% mol) and canola oil (65% mol). High levels of polyunsaturated linoleic acid (ω-6) were identified in soybean oil (45% mol) and corn oil (43.8% mol). Small proportions of α-linolenic acid (ω-3) were identified in soybean oil (8.6% mol), canola (8.4% mol) and palm oil (4.6% mol). Heat treatments indicated greater stability for olive and canola oils, which showed only 19 and 7% reduction in iodine content. In soybean and corn oil, aldehydes were mainly detected in the trans configuration, in addition to cis-trans-alkadienals, trans-trans-alkadienals and 4-oxo-alkanals. Palm oil, despite its high molar content of saturated fatty acids, showed a tendency to produce alkadienals and unsaturated aldehydes, due to the presence of 4.6% of α-linolenic acid. Based on the previous results observed in this study, it is recommended canola and olive oil for frying purposes.